Cytoskeletal Proteins of Actinobacteria - Michal Letek; María Fiuza; Almudena F. Villadangos; Luís M. Mateos; José A. Gil (International Journal of Cell Biology)
Although bacteria are considered the simplest life forms, we are now slowly unraveling their cellular complexity. Surprisingly, not only do bacterial cells have a cytoskeleton but also the building blocks are not very different from the cytoskeleton that our own cells use to grow and divide. Nonetheless, despite important advances in our understanding of the basic physiology of certain bacterial models, little is known about Actinobacteria, an ancient group of Eubacteria. Here we review current knowledge on the cytoskeletal elements required for bacterial cell growth and cell division, focusing on actinobacterial genera such as Mycobacterium, Corynebacterium, and Streptomyces. These include some of the deadliest pathogens on earth but also some of the most prolific producers of antibiotics and antitumorals.